2007
DOI: 10.1111/j.1440-1673.2007.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactate quantification by proton magnetic resonance spectroscopy using a clinical MRI machine: A basic study

Abstract: The purpose of this study was to establish quantification method of lactate concentration by proton magnetic resonance spectroscopy (MRS) carried out using a conventional 1.5-T MRI machine. We used a lactate phantom with known concentrations (1, 1.5, 3, 6, 12 and 14 mmol/L). As a clinical example, a patient with mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MELAS) was evaluated. Proton MRS was carried out using a clinical 1.5-T super-conducting magnetic resonance whole-body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…myo-inositol, choline, creatine, and NAA). In mitochondrial diseases, lactate elevations are suggested to range from 3−11 mM (Wilchowski et al, 1999) with other studies reporting average levels of approximately 6 mM (Saitoh et al, 1998;Isobe et al, 2007). The most consistent MRS change accompanying increased lactate in mitochondrial disease is decreased NAA, suggestive of cellular compromise.…”
Section: Mrs In Mitochondrial Diseases: Lactate and Naa Changesmentioning
confidence: 82%
“…myo-inositol, choline, creatine, and NAA). In mitochondrial diseases, lactate elevations are suggested to range from 3−11 mM (Wilchowski et al, 1999) with other studies reporting average levels of approximately 6 mM (Saitoh et al, 1998;Isobe et al, 2007). The most consistent MRS change accompanying increased lactate in mitochondrial disease is decreased NAA, suggestive of cellular compromise.…”
Section: Mrs In Mitochondrial Diseases: Lactate and Naa Changesmentioning
confidence: 82%
“…Previous reports have shown that MRS is a useful tool for the noninvasive detection of an LP in the brain parenchyma and in the ventricles. 6,8,12 Isobe et al 17 performed an in vitro study that showed a correlation between lactate concentration in a phantom and its quantification by MRS, and they demonstrated the reliability of MRS in LP detection. In our study of patients suspected of having mitochondrial disorders, we were able to quantify an LP by MRS in the lateral ventricles of all studied patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the correct clinical presentation, lactate elevations above normal levels of 1 mM can aid in determining whether ETC function is normal or compromised. Marked elevations can be observed in many patients with mitochondrial disease and ranging from 3 to 11 mM [Wilichowski et al, 1999], with some studies reporting average levels of 6 mM [Saitoh et al, 1998;Isobe et al, 2007]. Three examples illustrating markedly elevated brain lactate are shown in Figure 7.…”
Section: Biochemical Changes In Mitochondrial Diseasementioning
confidence: 93%